Characterization of Dialium Guianense fruits grown in the Northern Region of Brazil (Research, Society and Development, 2021)
Dialium Guianense, popularly known as Pororoca or Jutaí, is an exotic fruit cultivated in areas of the Amazon region. This work aimed to carry out the biometric and physicochemical characterization of Dialium Guyanense fruits. For the evaluation of biometric parameters, twenty whole fruits were weighed and measured (length and width) individually. Color analysis was performed using a Delta colorimeter. The proximate composition and caloric value of the fruit pulp were determined by analyzing moisture, ash, lipids, crude protein, crude fiber and carbohydrates. The result of the biometric parameters and color analysis showed that the pororoca is a small fruit (21.09 x 12.18 mm and 0.82 g) with a brown skin and orange colored pulp. As for the results of the chemical composition, the pororoca pulp presented 28.26% moisture; 71.74% dry matter; 3.37% ash; 0.45% lipids; 2.77% crude protein; 5.07% crude fiber; and 60.07% carbohydrate. The caloric value estimate revealed that the fruit has 255 kcal g-1. It is concluded that the physicochemical characterization becomes important for providing data that can be used by industries to obtain new food products.